2006
DOI: 10.1128/jvi.01536-06
|View full text |Cite
|
Sign up to set email alerts
|

Structurally Mapping the Diverse Phenotype of Adeno-Associated Virus Serotype 4

Abstract: The adeno-associated viruses (AAVs) can package and deliver foreign DNA into cells for corrective gene delivery applications. The AAV serotypes have distinct cell binding, transduction, and antigenic characteristics that have been shown to be dictated by the capsid viral protein (VP) sequence. To understand the contribution of capsid structure to these properties, we have determined the crystal structure of AAV serotype 4 (AAV4), one of the most diverse serotypes with respect to capsid protein sequence and ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
278
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 173 publications
(292 citation statements)
references
References 68 publications
14
278
0
Order By: Relevance
“…It is exceedingly difficult to predict which capsid regions should be reengineered to form novel viral-cell interactions that would be optimal to transduce particular tissues, despite advances in understanding AAV structure and function (37)(38)(39)(40). However, the search for AAV variants with novel properties through a variety of algorithms-such as isolating naturally occurring AAV, site-directed mutants, or (most recently) laboratory-evolved variants-has yielded various chimeric AAV viruses with distinct transduction profiles (17,(41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…It is exceedingly difficult to predict which capsid regions should be reengineered to form novel viral-cell interactions that would be optimal to transduce particular tissues, despite advances in understanding AAV structure and function (37)(38)(39)(40). However, the search for AAV variants with novel properties through a variety of algorithms-such as isolating naturally occurring AAV, site-directed mutants, or (most recently) laboratory-evolved variants-has yielded various chimeric AAV viruses with distinct transduction profiles (17,(41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…These AAV serotypes exhibit different infectivities on various tissues. Three-dimensional (3D) structure and mutagenesis studies of several AAV serotypes have shown that the common capsid region displays an 8-stranded (bB-bI) core ␤-barrel motif with loop insertions, which are the main determinants of AAV serotypespecific properties, such as receptor recognition, transduction efficiency and antigenic reactivity (15)(16)(17). The structural information on the capsid forms the basis for genetic engineering of novel AAV vectors.…”
mentioning
confidence: 99%
“…The VP3 topology contains a core eightstranded (␤B to ␤I) ␤-barrel motif and large loop insertions between the ␤-strands which form the surface of the capsid. Conformational variations in these surface loops (VR-I to VR-IX [22]) define the unique surface features for the each of the six representative AAV capsid structures, AAV2, AAV3B, AAV4, AAV6, AAV8, and AAV9, previously determined by X-ray crystallography (21-23, 26, 27, 29).Several wild-type AAV isolates as well as chimeras generated by directed evolution or rational mutagenesis are actively being developed for gene delivery applications (e.g., reviewed in reference 2). Transgenes packaged within the prototype human serotype…”
mentioning
confidence: 99%